# Math

What is the shortest distance between the circles defined by x^2-10x +y^2-4y-7=0 and x^2+14x +y^2+6y+49=0?

1. 👍 0
2. 👎 0
3. 👁 189
1. check what I just answered.

1. 👍 0
2. 👎 0
posted by Damon
2. http://www.jiskha.com/display.cgi?id=1460217578

1. 👍 0
2. 👎 0
posted by Damon

## Similar Questions

1. ### Graphing Ciricles

What is the shortest distance between the circles defined by x^2-10x +y^2-4y-7=0 and x^2+14x +y^2+6y+49=0? Thank you

asked by Candice on April 9, 2016
2. ### maths

show that the circles x^2 + y^2 - 10x - 8y + 18 = 0 and x^2 + y^2 - 8y - 4y +14x = 0 do not intersect

asked by Anonymous on May 2, 2017
3. ### Maths

show that the circles x^2 + y^2 - 10x - 8y + 18 = 0 and x^2 + y^2 - 8y - 4y + 14x = 0 do not intersect

asked by Joe on May 2, 2017
4. ### Maths

show that the circles x^2 + y^2 - 10x - 8y + 18 = 0 and x^2 + y^2 - 8x - 4y + 14x = 0 do not intersect.

asked by John on May 2, 2017
5. ### Maths

show that the circles x^2 + y^2 - 10x - 8y + 18 = 0 and x^2 + y^2 - 8x - 4y + 14x = 0 do not intersect. Apologies on behalf of my friend

asked by Matt on May 2, 2017
6. ### math,factoring,help

Can someone please show me step by step how to do these. I've read the book and there examples and It is just not clicking. Directions: Factor each of the following polynomials completely Problem:#1 14x^2-20x+6 Directions:Find all

asked by Jasmine20 on January 31, 2007

Please take a look at my work and let me know if I made any mistakes. You don't have to give me the answers. I'd just like to know if I made any mistakes so that I can correct them. Thanks! 1. 3x – 7 = 8 + 7 +7 3x = 15 3 3 x=5

asked by Ediese on June 12, 2006
8. ### math help pls pls pls

Given f(x) = 4x + 13 and g(x) = 10x − 2, solve for (f + g)(x) and select the correct answer below. (f + g)(x) = 14x + 15 (f + g)(x) = 14x + 11 (f + g)(x) = 6x + 11 (f + g)(x) = 6x + 15 is it b pls help me

asked by Oscar on March 31, 2016
9. ### Math

Can someone please check my answers below for accurateness? The instructions are: Differentiate and simplify. 1) y=(2x^2+3x-1)(3x^2-5x-3) y'=(4x+3)(3x^2-5x-3)+(2x^2+3x-1)(6x-5) 2) y=(5x^2+3x-1)(3x^2-5x-3)

asked by Christine on August 7, 2009